Pengaruh Beban Pajak Tangguhan, Beban Pajak Kini, dan Perencanaan Pajak dalam Mendeteksi Manajemen Laba - Widyastuti, Radilla; Hasan, Amir; Rasuli, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The aim of this research is to predict and explain the effect of competency, accountability and independency on audit quality, moderated by due professional care and professional skepticism. The research sample is Auditors of Inspectorate which are located in Riau Province as much as 13 Inspectorates. The sampling technique used purposive approach. The data used primary data obtained from questionnaire, as a part of explanatory/confirmatory research. Data analysis method by using Partial Least Square (PLS), assisted by WarpPLS 6.0 application. Hypothesis testing is performed using the path coefficients to examine the effect of each independent variable on the dependent variable partially, and effect size to determine the effect of the moderate variable in the model. The results of this research indicate that only independence has a significant effect directly on audit quality. Due Professional Care is able to moderate the relationship between competence, independence and accountability to Audit quality. As another moderate variable, Professional Skepticism cannot be used because it is statistically identical to Due Professional Care. The coefficient determination of 56,4% shows the change in audit quality is explained by the determinant variables used in this study, while the other (43,6%) described by other variables